Broadcast Journalism - Coffey, M. (Encyclopedia of Applied Ethics, 2012)
Like print journalism, the aim of broadcast journalism is to distribute information to public audiences. Accordingly, ethical considerations with respect to both forms of journalism are primarily the same, although broadcasting has always been the subject of more stringent regulation. Due to its power as an advertising medium, broadcasting in the United States has been developed under a commercial model. Conversely, in Britain, it operates as a public service utility. Modern phenomena such as free market ideology and technological progress have contributed to the development of broadcast journalism, and it is with respect to such factors that the ethical stance of the broadcast journalist must be considered. The complex relationship among journalists, medium, and the world they seek to describe has led to the introduction of a professional code of ethics, designed to maintain the integrity and objectivity of the press.